Body mass management of lightweight rowers: nutritional strategies and performance implications - Slater, G.; Rice, A.; Jenkins, D.; Hahn, A. (British Journal of Sports Medicine, 2014)
The majority of lightweight rowers undertake acute weight loss prior to competition. Given the competitive advantage afforded to larger, more muscular rowers over their smaller counterparts, the use of moderate, acute weight loss may be justified, at least among larger, leaner athletes who struggle to achieve the specified body mass requirement and have limited potential for further body mass loss via reductions in body fat. The performance implications of moderate acute weight loss appear to be small on the ergometer and may be even less on water, at least when aggressive recovery strategies are adopted between weigh-in and racing. Furthermore, any performance implications of acute weight loss are not exacerbated when such weight loss is undertaken repeatedly throughout the course of a regatta, and may even be eliminated when aggressive recovery strategies are introduced before and after racing. The combination of adequate sodium, fluid and carbohydrate in line with current guidelines results in the best performances. While the performance implications of modest acute weight loss may still need to be considered in regard to competition outcome, chronic body mass strategies may not be without performance implications. This is especially the case for athletes who have very low levels of body fat and/or athletes who decrease their body mass too quickly. Further studies are needed to address the degree of weight loss that can be tolerated with minimal health and/or performance implications, and the optimal time frame over which this should occur. Possible adaptation to the physiological state that accompanies acute weight loss also warrants investigation.